Islamic Renewal and Reformation - Haqq, Muhammad Valiyyul; Rahimin Affandi Abdul, Rahim (FOCUS, 2024)
This article discusses the renewal of civilization which is an integral part of Islamic thought. Using the qualitative analysis method, this literature review found several things about the meaning, meaning and origins of renewal in Islamic history. The relationship between the renewal of thought and the concept of ijtihad is also discussed, as well as how this renewal is manifested in the writings of Islamic thinkers. This article develops reform formulations and guidelines that contemporary Muslims must strive for in articulating the goal of harmony between civilizations and their cooperation for the common good.